Determination of cilostazol and its active metabolite 3,4-dehydro cilostazol from small plasma volume by UPLCâMS/MS - Nejal M. Bhatt; Vijay D. Chavada; Daxesh P. Patel; Primal Sharma; Mallika Sanyal; Pranav S. Shrivastav (Elsevier, 2015)
A simple, rapid and sensitive ultra performance liquid chromatography-tandem mass spectrometry (UPLCâMS/MS) method has been developed for the simultaneous determination of cilostazol and its pharmacologically active metabolite 3,4-dehydro cilostazol in human plasma using deuterated analogs as internal standards (ISs). Plasma samples were prepared using solid phase extraction and chromatographic separation was performed on UPLC BEH C18 (50Â mmÃ2.1Â mm, 1.7Â Âµm) column. The method was established over a concentration range of 0.5â1000Â ng/mL for cilostazol and 0.5â500Â ng/mL for 3,4-dehydro cilostazol. Intra- and inter-batch precision (% CV) and accuracy for the analytes were found within 0.93â1.88 and 98.8â101.7% for cilostazol and 0.91â2.79 and 98.0â102.7% for the metabolite respectively. The assay recovery was within 95â97% for both the analytes and internal standards. The method was successfully applied to support a bioequivalence study of 100Â mg cilostazol in 30 healthy subjects. Keywords: Cilostazol, 3,4-dehydro cilostazol, UPLCâMS/MS, Sensitive, High throughput